PENGUNGKAPAN PELAPORAN KEUANGAN SEGMEN PT BAYU TBK PERIODE TAHUN 2018-2022 - Yustian Pemersatu Zebua; Riska Saputri; Risa Hartini; Shavira Rizki Maharani (Jurnal Ekonomi Sakti, 2023)
Thei disclosuirei of financial stateimeints is onei of thei obligations for puiblicly listeid companieis tobei accouintablei for thei uisei of opeirational buidgeits within a speicific peiriod. In this casei, seigmeintreiporting is a reiqui ireid reiport to bei discloseid by thei company. Seigmeint reiporting provideisinformation abouit inveistmeint opportuinitieis.This reiseiarch was condui cteid on PT Tei lkom Indoneisia Tbk for thei peiriod of 2020-2021 uising aquiantitativei meithod. Thei meithod involveis teisting reiveinuiei, teisting asseits, and teisting a teinpeirceint profit to ideintify which seigmeint reiporting dominateis thei disclosuirei. Additionally, theireiseiarch aims to ideintify thei uisei of PSAK No. 5 (Seigmeint Reiporting) standards.Thei reiseiarch findings indicatei that not all componeints of PT Tei lkom Indoneisia Tbk's buisineissseigmeints arei incluideid in thei seigmeint reiporting. Howeiveir, thei incluision of additional seigmeintsin thei reiporting is not neiceissary. Fuirtheirmorei, thei seigmeint reiporting of buisineiss seigmeints isin compliancei with thei PSAK No. 5 reiporting standards.